The Effect of Adding Glass Powder Waste And Superplasticizier On Concrete Compressive Strength - Lukhvi Dian Basiroh Hutasuhut; Dedy Rutama; Ribut Nawang Sari (Jakarta Global University, 2025)
This study investigates the effect of glass powder as a partial replacement for fine aggregate on the physical properties and compressive strength of concrete. The experimental program included bulk density testing, moisture content analysis, mix design development, slump testing, and compressive strength testing at the age of 28 days with a target strength of K-250. Glass powder was incorporated at replacement levels of 0%, 2%, 4%, and 8% by weight of fine aggregate, while a superplasticizer was used to maintain workability. The results indicate that fine aggregate has the highest unit weight, followed by coarse aggregate, whereas glass powder exhibits the lowest unit weight. Moisture content results show that coarse aggregate has the highest moisture content, while glass powder has the lowest. Slump test results demonstrate that all concrete mixtures achieved acceptable workability, with slump values ranging from 9 to 11 cm. Compressive strength testing shows that normal concrete achieved the highest strength, while the inclusion of glass powder led to a reduction in strength, particularly at higher replacement levels. However, the mixture with 4% glass powder showed relatively better performance compared to other glass powder variations. Overall, the study concludes that glass powder can be used as a partial fine aggregate replacement in concrete at controlled percentages without significantly compromising workability and with acceptable early-age strength performance.